Kinetics of Reactive Blue 21 Decolorization Using Peracetic Acid - Chieu, Le Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 3DO - 10.25073/2588-1094/vnuees.4106, 2017)
Decolorization rate of Reactive Blue 21 by peracetic acid in aqueous solutions was measured at pH 6.0. Concentrations of peracetic acid were applied in the range of 1 - 3 mM. The reaction kinetics were monitored by recording the light absorption of the Reactive Blue 21 at 660 nm. The obtained results showed that the decolorization happened via non-catalytic and auto-catalytic reactions. Both the reactions were proposed to obey the second-order rate law. Keywords Reactive Blue 21, peracetic acid, kinetics, catalyst, decolorization References [1] V. K. Gupta; S. Khamparia; I.Tyagi; D. Jaspal; A. Malviya, Decolorization of mixture of dyes: A critical review, Global J. Environ. Sci. Manage., 1 (1) (2015) 71. [2] Siew-Teng Ong, Pei-Sin Keng, Weng-Nam Lee, Sie-Tiong Ha, Yung-Tse Hung, Dye Waste Treatment, Water, 3 (2011) 157. [3] Srebrenkoska Vineta, Zhezhova Silvana, Risteski Sanja, Saska Golomeova, Methods for waste waters treatment in textile industry, International scientific conference, November 2014, Gabrovo. [4] Maria Cristina Silva, Angelita Duarte Corrêa, Maria Teresa Sousa Pessoa Amorim, Píer Parpot Juliana Arriel Torres, Pricila Maria Batista Chagas, Decolorization of the phthalocyanine dye reactive blue 21 by turnip peroxidase and assessment of its oxidation products, Journal of Molecular Catalysis B:Enzymatic 77 (2012) 9.